Financing electoral campaigns according to the 21/01 organic law relating to electoral system. - Ghaoues, Hassina (Journal of Human Sciences, 2022)
Financing elections has a great importance.It is a fundemental factor which can guide the results in favor of some members or political parties rather than others.This is illegal and illegitimate . Therefore,for fear of resorting to illegal financial sources ,and in order to avoid suspicious fina,cing and the use of corrupt money in the elections, the legislator,along the lines of comparative legislation, reconsidered the financing of electoral campain in accordance with organic law 21/01 to strict legislative regulation and strict control, and the installation of a special committee to remove corrupt money from politics and to ensure the principle of equality and equal opportunities for all candidates.